2017
DOI: 10.3892/ol.2017.6076
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 217 inhibits cell proliferation and enhances chemosensitivity to doxorubicin in acute myeloid leukemia by targeting KRAS

Abstract: Abstract. Acute myeloid leukemia (AML) is a heterogeneous malignant disorder derived from the myeloid hematopoietic cells that accounts for ~80% of all adult acute leukemia. Numerous studies have shown that drug resistance not only exists against conventional chemotherapeutic drugs, but also limits the efficacy of new biological agents. Therefore, it is important to identify the mechanisms behind chemoresistance and seek therapeutic strategies to enhance efficacy in AML chemotherapy. MicroRNA (miR)-217 has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 37 publications
(42 reference statements)
0
31
0
Order By: Relevance
“…miRNAs are a subset of small noncoding RNAs that control gene expression in a site-specific manner (15). Accumulating evidence has identified the distinct expression patterns and biological functions of miRNAs in biological processes, including cell differentiation, apoptosis, and metabolism (16).…”
mentioning
confidence: 99%
“…miRNAs are a subset of small noncoding RNAs that control gene expression in a site-specific manner (15). Accumulating evidence has identified the distinct expression patterns and biological functions of miRNAs in biological processes, including cell differentiation, apoptosis, and metabolism (16).…”
mentioning
confidence: 99%
“…In leukaemia cells, it has been demonstrated that several types of microRNAs exert roles. For example, MicroRNA 217 inhibits leukaemia cell proliferation and enhances chemosensitivity . Downregulation of miR‐224 contribute to cell survival and chemoresistance in chronic myeloid leukaemia cells .…”
Section: Discussionmentioning
confidence: 99%
“…For example, MicroRNA 217 inhibits leukaemia cell proliferation and enhances chemosensitivity. 19 Downregulation of miR-224 contribute to cell survival and chemoresistance in chronic myeloid leukaemia cells. 20 There are some reports indicating the correlation between HoxA9 and microRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Group 1 characterized with high level of expression of sncRNAs, which associated with sensitivity to therapy. This group members are miRNA-181a, b; let-7f, miRNA-9*, miRNA-96, miRNA-135a, miRNA-409, miRNA-10, miRNA29b and miRNA-217 [72,73,[97][98][99][100]. Group 1 members act through activation of cellular differentiation, inhibition of leukemic cells proliferation and survival, regulation of cell cycle, inducing of apoptosis and suppression of migration and invasion.…”
Section: Sncrnas As Markers Of Therapeutic Resistance or Sensitivity mentioning
confidence: 99%
“…It targets KRAS regulator of signaling links from extracellular space to the nucleus. KRAS connects multiple upstream signals to various downstream signaling pathways [97].…”
Section: Sncrnas As Markers Of Therapeutic Resistance or Sensitivity mentioning
confidence: 99%